Non-amplified impedimetric genosensor for quantification of miRNA-21 based on the use of reduced graphene oxide modified with chitosan - López Mujica, Michael Earvin (2021)
We report here an impedimetric genosensor for the quantification of microRNA-21 using [Fe(CN)6]3−/4− as redox probe to transduce the hybridization event. The biosensing platform was built at a thiolated-gold electrode by covalent bond of reduced graphene oxide (RGO) modified with chitosan (CHIT) and further covalent attachment of the aminated DNA probe. GO was used to provide the carboxylic groups for the covalent attachment of CHIT and, once reduced, to improve the electroactivity of the resulting platform, while CHIT served as a bridge between the thiol and the aminated probe DNA. The proposed bioanalytical platform allows the label-free, non-amplified, simple and fast biosensing of microRNA-21, with a linear range between 1.0 × 10−12 M and 1.0 × 10−8 M, a sensitivity of (134 ± 4) ΩM−1 (r2 = 0.996), a detection limit of 300 fM, and a reproducibility of 5.9% for 1.0 × 10−12 M miRNA-21 and 2.2% for 1.0 × 10−9 M miRNA-21. The genosensor was successfully used for the quantification of microRNA-21 in enriched human blood serum, urine and saliva samples.